Computer Image Analysis of the Ocular Fundus - Pe’er, J.; Zajicek, G. (Methods of Information in Medicine, 1982)
Photographic transparencies of the ocular fundus were scanned with an image dissector under computer control. The image is digitized into 400 X 400 points each exhibiting 256 gray level values. During analysis, the computer stores in its buffer only five consecutive lines upon which image processing is performed; only then is the first line projected on the scope and the following line (the sixth in the original image) introduced into the buffer. In this setup, digitization may be manipulated on-line in real time.
Keywords: Image Processing; Pattern Recognition; Ocular Fundus; Optic Disc